Essential oils as multicomponent mixtures and their potential for human health and well-being - Bunse, Marek; Daniels, Rolf; Gründemann, Carsten; Heilmann, Jörg; Kammerer, Dietmar R.; Keusgen, Michael; Lindequist, Ulrike; Melzig, Matthias F.; Morlock, Gertrud E.; Schulz, Hartwig; Schweiggert, Ralf; Simon, Meinhard; et al. (Frontiers in pharmacology, 2022)
Essential oils (EOs) and their individual volatile organic constituents have been an inherent part of our civilization for thousands of years. They are widely used as fragrances in perfumes and cosmetics and contribute to a healthy diet, but also act as active ingredients of pharmaceutical products. Their antibacterial, antiviral, and anti-inflammatory properties have qualified EOs early on for both, the causal and symptomatic therapy of a number of diseases, but also for prevention. Obtained from natural, mostly plant materials, EOs constitute a typical example of a multicomponent mixture (more than one constituent substances, MOCS) with up to several hundreds of individual compounds, which in a sophisticated composition make up the property of a particular complete EO. The integrative use of EOs as MOCS will play a major role in human and veterinary medicine now and in the future and is already widely used in some cases, e.g., in aromatherapy for the treatment of psychosomatic complaints, for inhalation in the treatment of respiratory diseases, or topically administered to manage adverse skin diseases. The diversity of molecules with different functionalities exhibits a broad range of multiple physical and chemical properties, which are the base of their multi-target activity as opposed to single isolated compounds. Whether and how such a broad-spectrum effect is reflected in natural mixtures and which kind of pharmacological potential they provide will be considered in the context of ONE Health in more detail in this review.
Gesehen am 31.10.2022